Scroll atau Belajar? Tugas Tertunda di Era Digital: Pengaruh Kontrol Diri dan Adiksi Media Sosial pada Prokrastinasi Akademik Remaja Awal - Lintang Puspitasari; Nita Rohayati; Devi Marganing Tyas (Pusat Riset dan Inovasi Nasional, 2024)
The increasing use of social media among adolescents often results in procrastination. Adolescents with low self-control tend to have difficulty managing study time, are easily distracted by social media notifications, and ultimately lead to academic procrastination. This study aims to determine the effect of self-control and social media addiction on academic procrastination in early adolescents. This study involved 400 early adolescents aged 13 to 17 years in Karawang Regency using a quantitative approach and causality design. The instruments used were the Brief Self-Control Scale (BSCS), the Bergen Social Media Addiction Scale (BSMAS), and the Academic Procrastination Scale (APS). Data analysis was performed using multiple linear regression with the help of SPSS version 26. The results of the simultaneous test showed that self-control and social media addiction together had a significant effect on academic procrastination (p = 0.000 < 0.05). The partial test results showed that self-control significantly influenced academic procrastination (p = 0.000 < 0.05) and social media addiction also significantly influenced academic procrastination (p = 0.000 < 0.05). These findings emphasize the importance of strengthening self-control and reducing dependence on social media as strategies to reduce academic procrastination in early adolescents.